Kapasitas Memori Kerja dalam Pengambilan Keputusan - M. Dinah Charlota Lerik (Faculty of Psychology Universitas Gadjah Mada, 2016)
This paper will discussed the working memory model developed by Baddeley and Hitch. Baddeley’s claimed that working memory consists of three components: the central executive and the two slave systems, the phonological loop and visuospatial sketchpad. The other model is created by Cowan, which assumes that working memory includes a number of processes that can keep a limited amount of information accessible for a limited amount of time. To test a person’s working memory capacity, there have been many working memory span tasks. Few experiment will be discused about the amount of working memory load determines the heuris tic by a person who make decision, determine the conjuction fallacy and judgment.